Names of geologists eternalized in names of minerals - Grechischev, Oleg K. (The New Research of Tuva, 2011)
Minerals, as well as mountain systems, islands, straits, cities and ships, keep eternalized in their names the names of geologists whose achievements and humble activities have left their traces in people’s memory.
Keywords: Geology; Mineralogy; microscope; tuvit; kralovic; Lavrentieva; Kuznetsova; Telepaisa ore zone; field Arzak; mercury; Nickel-cobalt Deposit